Hubungan Usia Menarche Dengan Usia Menopause Pada Wanita Di Desa Purworejo Kecamatan Bae Kabupaten Kudus - Setiawati, Indayana; Kumala, Tiara Fatma; Ulfa, Happy Maria (Journal of Midwifery Science: Basic and Applied Research, 2024)
The age of menopause is influenced by many factors, presumably one of which is the age of menarche. There are different opinions regarding the relationship between the age of menarche and the age of menopause. Some studies have found that there was relationship between menarche age and menopause age, but some other studies have found the opposite. From the results of preliminary studies in the elderly posyandu of Purworejo Village, 30 respondents were obtained, of which 3 respondents experienced precocious menopause with early menarche and 27 respondents experienced normal menopause with normal menarche. This study aims to determine the relationship between menarche age and menopause age in women in RW 01 Purworejo Village, Bae District, Kudus Regency. This study used quantitative research methods with Cross Sectional approach. The population taken was women who entered menopause in RW 01 Purworejo Village, Bae District, Kudus Regency. The total population was 234 with a sample size of 100 respondents by purposive sampling. The results of statistical analysis using the Chi Square test obtained an asym.sig value of 0.626> 0.05, it can be interpreted that H0 is accepted and Ha is rejected, so there is no significant relationship between menarche age and menopause age.Keywords : Age of Menarche; Age of Menopause